2019
DOI: 10.1038/s41598-018-38363-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive in vivo fluorescence imaging of apoptotic retinal photoreceptors

Abstract: Phosphatidylserine externalization is an early molecular signature for apoptosis. In many retinal degenerative diseases, photoreceptor neurons die by apoptosis. Here, we report utility of the phosphatidylserine-binding conjugate of Bis(zinc(II)-dipicolylamine (Zn-DPA) with Texas-red (PSVue-550) in transiently labeling apoptotic photoreceptors in living pigmented or albino rats and mice with retinal degeneration. Applying PSVue-550 as eyedrop is non-toxic and eliminates need for intraocular injection. PSVue-550… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 25 publications
2
32
1
Order By: Relevance
“…The b-wave indicative of activities of second order retinal neurons was also improved by tmx eye drop treatment ( Figure 5E). RCS rats with ongoing retinal degeneration do not show normal retinal activity in ERG recordings with consistent increases in a-and b-wave amplitudes in response to light flashes of increasing intensity (23). Recording at P33 specifically in our study we observed flat or even moderately declining a-and b-wave amplitudes at highest flash intensities applied indicative of dysfunction of photoreceptors at this age.…”
Section: Suppression Of Microglia By Tamoxifen Eye Drops Mitigates Phcontrasting
confidence: 52%
See 3 more Smart Citations
“…The b-wave indicative of activities of second order retinal neurons was also improved by tmx eye drop treatment ( Figure 5E). RCS rats with ongoing retinal degeneration do not show normal retinal activity in ERG recordings with consistent increases in a-and b-wave amplitudes in response to light flashes of increasing intensity (23). Recording at P33 specifically in our study we observed flat or even moderately declining a-and b-wave amplitudes at highest flash intensities applied indicative of dysfunction of photoreceptors at this age.…”
Section: Suppression Of Microglia By Tamoxifen Eye Drops Mitigates Phcontrasting
confidence: 52%
“…Animals of both sexes were used. Wild-type (WT) and mertk −/− mice in the same 129T2/SvEmsJ genetic background ( 23 ), pink-eyed dystrophic RCS rats (rdy/rdy-p) and Sprague Dawley (SD) WT rats were raised to yield litters at defined age for experiments. For tissue harvest, animals were euthanized by CO 2 asphyxiation before immediate eye enucleation and processing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Once activated by zinc, PSVue has fast, calcium-independent binding kinetics; is significantly smaller in size compared to annexin-based probes, and, similarly to ANXV, is cell impermeable, thus labeling only PS that has been externalized (Smith et al, 2011). While PSVue has been used previously to monitor cell death in vivo in several disease and injury models (Chan et al, 2015;Mazzoni et al, 2019;Smith et al, 2012), it remains unknown whether localized, non-apoptotic PS exposure occurs in vivo.…”
Section: Ps Is Exposed At Synapses In Vivo In the Developing Hippocampusmentioning
confidence: 99%